2021
DOI: 10.1099/mgen.0.000596
|View full text |Cite
|
Sign up to set email alerts
|

Genomic diversity, life strategies and ecology of marine HTVC010P-type pelagiphages

Abstract: SAR11 bacteria dominate ocean surface bacterioplankton communities, and play an important role in marine carbon and nutrient cycling. The biology and ecology of SAR11 are impacted by SAR11 phages (pelagiphages) that are highly diverse and abundant in the ocean. Among the currently known pelagiphages, HTVC010P represents an extremely abundant but under-studied phage group in the ocean. In this study, we have isolated seven new HTVC010P-type pelagiphages, and recovered 77 nearly full-length HTVC010P-type metagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 67 publications
(136 reference statements)
3
21
0
Order By: Relevance
“…Recently, the presence of temperate phage in oligotrophic Pelagibacter species has been validated (28,29), consistent with our observations of phage satellites in the genomes of this ubiquitous bacterioplankton group. Similarly, cyanophages of Prochlorococcus often encode integrases, which allows them to integrate into host genomes (30).…”
Section: Marine Phage Satellites Are Ubiquitous and Abundant In The O...supporting
confidence: 90%
See 1 more Smart Citation
“…Recently, the presence of temperate phage in oligotrophic Pelagibacter species has been validated (28,29), consistent with our observations of phage satellites in the genomes of this ubiquitous bacterioplankton group. Similarly, cyanophages of Prochlorococcus often encode integrases, which allows them to integrate into host genomes (30).…”
Section: Marine Phage Satellites Are Ubiquitous and Abundant In The O...supporting
confidence: 90%
“…Specifically, the most prevalent cellular hosts of surface water marine VEIMEs were Pelagibacter and the cyanobacterium Prochlorococcus , among the most abundant bacterial groups present in open ocean surface waters (26, 27). Recently, the presence of temperate phage in oligotrophic Pelagibacter species has been validated (28, 29), consistent with our observations of phage satellites in the genomes of this ubiquitous bacterioplankton group. Similarly, cyanophages of Prochlorococcus often encode integrases, which allows them to integrate into host genomes (30).…”
Section: Introductionsupporting
confidence: 90%
“…The enzyme is involved in the synthesis of sulfite from phosphoadenosine 5’-phosphosulfate (PAPS) and thus part of the sulfate reduction pathway ( Bick et al, 2000 ). The cysH gene has been identified in phages infecting members of the SAR11 clade, which lack the phosphoadenosine 5’-phosphosulfate reductase and other genes required in assimilatory sulfate reduction but has recently also been found to be generally widespread in marine phages ( Du et al, 2021 ; Kieft et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whole-genome alignment showed that the Skadi genome is arranged into early and late genomic regions similar to other HTVC010P-type genomes [27]. A TonB-dependent receptor protein located between the two tail tube proteins A and B and the major capsid protein suggests TonB as a putative receptor for adsorption and initiating infection [39,40] (Figure 1).…”
Section: Skadi Uses Host Rna and Dna Polymerases For Viral Replicationmentioning
confidence: 99%
“…Located within the direct terminal repeat region is a conserved TerL gene for packaging. For cell lysis, Skadi encodes a peptidase M15, similar to other HTVC010P-type pelagiphages [27]. Alignment of HTVC010P-type genomes showed that regions related to DNA replication and metabolism, as well as the terminase and phage head related proteins are conserved, using recommended amino acid identity (AAI) thresholds of >30% [38] (Supplementary Figure 1).…”
Section: Skadi Uses Host Rna and Dna Polymerases For Viral Replicationmentioning
confidence: 99%